The anxious body of modernism: Kafka, Hamsun, and Woolf - Pulkki, E (2018)
This thesis argues that psychological anxiety is a central narrative mechanism for modernist writing, and that this anxiety is expressed through the prominence of the body in texts. Through readings of Knut Hamsun’s Sult, Franz Kafka’s Der Verschollene, and Virginia Woolf’s Mrs Dalloway and its manuscript draft The Hours, I argue that anxiety as articulated in key modernist texts is more pervasive and differently distributed than previously thought. This thesis counteracts the predominant phenomenological approaches to the body in literary studies, which see the body as constitutive of identity, and emphasize bodily agency in writing and thought. Instead, I make the case for a psychologically informed, critical reading of the body through the concept of body image, the study of which began in the modernist period.